2022
DOI: 10.1001/jamaoto.2021.3982
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cigarette Smoking Patterns Over 30 Years With Audiometric Hearing Impairment and Speech-in-Noise Perception

Abstract: IMPORTANCEThe implications of cigarette smoking and smoking cessation for hearing impairment remain unknown. Many studies on this topic have failed to account for attrition among smokers in their findings.OBJECTIVE To assess the association of cigarette smoking patterns with audiometric and speech-in-noise hearing measures among participants of the Atherosclerosis Risk in Communities Study. DESIGN, SETTING, AND PARTICIPANTSThis cross-sectional study included participants of the Atherosclerosis Risk in Communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…Observed feature impacts on PTA align closely with reported results from prior clinical studies. In the abbreviated model, 4 of the 5 most influential features on an increased PTA were known risk factors for the development of HL: older age, male gender, cigarette smoking, and obesity 32‐36 . With the rising prevalence of obesity and diabetes mellitus, the impact of these conditions on HL remains an important consideration 37‐39 .…”
Section: Discussionmentioning
confidence: 99%
“…Observed feature impacts on PTA align closely with reported results from prior clinical studies. In the abbreviated model, 4 of the 5 most influential features on an increased PTA were known risk factors for the development of HL: older age, male gender, cigarette smoking, and obesity 32‐36 . With the rising prevalence of obesity and diabetes mellitus, the impact of these conditions on HL remains an important consideration 37‐39 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the aforementioned risk factors, evidence has been accumulated regarding the relationship between smoking and hearing loss in both cross-sectional 16 and longitudinal studies. 17 Furthermore, although diabetes mellitus is considered a risk factor for hearing loss, some studies have reported that no such relationship exists when the associations are adjusted for age, biological sex, and hypertension. 18 However, others have found that diabetes is an independent risk factor for hearing impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Our second research question was regarding whether the risk factors associated with hearing loss, such as smoking, hypertension, and diabetes mellitus, along with the severity of the COVID‐19 infection would exacerbate the deterioration in hearing thresholds post‐COVID‐19. Among the aforementioned risk factors, evidence has been accumulated regarding the relationship between smoking and hearing loss in both cross‐sectional 16 and longitudinal studies 17 . Furthermore, although diabetes mellitus is considered a risk factor for hearing loss, some studies have reported that no such relationship exists when the associations are adjusted for age, biological sex, and hypertension 18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations